PERKEMBANGAN AGEN PERJALANAN WISATA HALAL INDONESIA - Dina Hariani (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2024)
Halal tourism is a growing trend worldwide today. The development of Halal tourism in Indonesia can be seen, for example, in the numerous travel agencies offering Halal tour packages abroad. Muslim-majority destinations such as Uzbekistan, Turkey, Dubai, and Saudi Arabia are popular among Indonesian Muslim tourists. Additionally, non-Muslim countries like Japan, Korea, England, and European countries are also visited by Indonesian Muslim travelers. This study examines 10 Indonesian travel agencies that sell Halal tour packages. Through observation and literature review, it was found that travel agencies in Indonesia predominantly offer Halal tour packages abroad rather than domestically. These Halal tour packages typically include Halal food availability, maintained prayer times, and activities compliant with Islamic law. The countries visited by Indonesian Muslim tourists are also among the top destinations for Muslim travelers globally